Conflict resolution in trajectory-based air traffic flow management - Low, Eugene Yong Yee. (2013)
Air Traffic Flow Management (ATFM) is the process of routing and scheduling air traffic. Currently, ATFM is performed on a clearance based system by the Air Traffic Controllers (ATC). Aircrafts in the airspace need to obtain clearances from the ATCs before any maneuver is carried out. In this system, the airspace is segregated into a network of imaginary corridors which does not optimize the total volume of the airspace available. Trajectory-based en-route traffic management is one of the alternative ATFM methods suggested to maximize the total volume of usable airspace that is available to the aircrafts. This paper aims to explore the various trajectory-based en-route traffic management methods suggested by various academic papers and select one that is most relevant to a three aircraft case. A model which aims to de-conflict aircrafts within the airspace by regulating the airspeed and the heading angle of the conflicting aircrafts is selected. This model was selected due to its robustness as it combines conflict detection and conflict resolution into one single formulation. A fictitious problem is formulated and the proposed algorithm is tested. The paper would also discuss the pros and cons that each formulation brings. Lastly, this paper would suggest areas for further research that was discovered during the course of this study.